The Changing Landscape of Ageing Workforce in Hong Kong – The Importance of ICT Training in Lifelong Corporate Learning - Lam, Sanches; Chung, Winnie (International Journal of Advanced Corporate Learning (iJAC), 2010)
To analyse the changing landscape of ageing workforce in Hong Kong and its needs of ICT training at both the individual worker level and the firm level. This study describes the decisions that older workers are actually making about work and retirement in order to understand the changing expectation of older employees when they reach the retirement age. A large scale of a purposive sample of over 500 aged 50 years or older employers completed an on-line survey. A selected sub-sample of 50 participated in follow-up in-depth interviews. It indicates that older workers are willing to contribute, but in a more flexible way and willing to learn ICT skills to retain active for both social and employment reasons. One important implication for many employers is that they have to redefine specific recruiting, retention and workplace strategies to address the different needs, priorities and preferences among older workers, and how to keep them productive and satisfied.